Eating the other : translations of the culinary code - Stano, Simona (Cambridge Scholars Publishing, 2015)
Food represents an unalienable component of everyday life, encompassing different spheres and moments. What is more, in contemporary societies, migration, travel, and communication incessantly expose local food identities to global food alterities, activating interesting processes of transformation that continuously reshape and redefine such identities and alterities. Ethnic restaurants fill up the streets we walk, while in many city markets and supermarkets local products are increasingly complemented with spices, vegetables, and other foods required for the preparation of exotic dishes. Mass.